Omnibus Law and Changes Regarding Specific Time Work Agreements (PKWT) in the Job Creation Act - Rini Fathonah; Heni Siswanto; Ahmad Irzal Fardiansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Omnibus law is a law in which it discusses and contains more than one discussion theme or topic. The omnibus law became the attention of the Indonesian people after the enactment of Law no. 11 of 2020 concerning Job Creation. Even before the law was passed, it had been rejected by the community. This is because people think the law will harm the small people, one of which is PKWT employees and will actually benefit the elite. Then what is the actual status of the omnibus law in Indonesia, considering that the technique has not been regulated in Law no. 12 of 2011 concerning the Establishment of Legislation which was changed to Law no. 15 of 2019. And what is the status of PKWT after the omnibus law regarding the work copyright law. In this study, the author uses a normative juridical research method. The results obtained in this study can be concluded that the application of omnibus law in Indonesia may be applied, but it would be better if before the enactment of the omnibus law, the legal basis was first made, considering that our country is a state of law. The omnibus law is also not the only way out in solving regulatory problems in Indonesia. This is because Indonesia's problems are not only about overlapping regulations, but there are many things that are not sufficiently resolved through the omnibus law. Then regarding PKWT there are five important points that must be considered with the existence of the Job Creation Act, namely the employee's tenure, contract extension, probationary period, compensation money and the form of a written agreement.